Relationship between Salivary Levels of Protein Carbonyl and Total Antioxidant Capacity and Prevalence of Dental Caries among Type 1 Diabetic Children: An Analytical Cross-Sectional Study - Shahad Fahim Obaid; Shahbaa Munther; Marwa Hasan Abbas (Dental Hypotheses, 2023)
Introduction: We aimed to assess the possible relationship between dental caries prevalence and oxidative stress markers such as protein carbonyl (PC) and total antioxidant capacity (TAOC) of saliva among type 1 diabetic children. Methods: An analytical cross-sectional study was performed among 45 type 1 diabetic children and compared with 45 healthy control children aged 10 to 12 years old. Dental caries was diagnosed and recorded using the decayed, missing, and filling index (DMFS/dmfs). Unstimulated salivary specimens were collected for evaluation of TAOC and PC using an enzyme-linked immune-sorbent assay (ELISA). A linear regression model and one-way ANOVA test were employed for data analysis using the R 4.3.0. Results: Salivary levels of TAOC and PC, having diabetes, and diabetes status (controlled or uncontrolled) were not statistically significant (P > 0.05) predicators regarding the prevalence of dental caries among type 1diabetic children. Conclusion: The diabetic status had a significant effect on salivary levels of TAOC and PC, but no significant effect on the prevalence of dental caries.